Major Discordant Structural Anomalies in Monochorionic Twins: Spectrum and Outcomes. (30th October 2018) - Rustico, Maria Angela; Lanna, Mariano; Faiola, Stefano; Casati, Daniela; Spaccini, Luigina; Righini, Andrea; Parazzini, Cecilia; Napolitano, Marcello; Scelsa, Barbara; Lista, Gianluca; Corti, Carla; Riccipetitoni, Giovanna; et al.
Abstract : Monochorionic twins, resulting from a single fertilized egg giving rise to two separate embryos, are monozygotic and considered genetically identical. However, discordant phenotypes have been reported in monozygotic twins. We analyzed a retrospective cohort of 155 monochorionic pregnancies (312 twins) with major discordant structural anomalies coded by the ICD-10 system in order to describe the spectrum of anomalies, the management of the pregnancies, and the perinatal outcome. Treatment options included conservative management, selective feticide with bipolar cord coagulation, or complete termination. All survivors underwent at least 24 months of postnatal follow-up. Discordancy was complicated by twin-to-twin transfusion syndrome in eight pregnancies (5%) and by selective intrauterine growth restriction in 41 (26%). Major structural anomalies affected one system in 139 cases (90%) and multiple systems in 16 (10%). Median gestational age at diagnosis was 19.1 weeks (IQR 16.4–21.3). The most frequent single-system anomalies involved the nervous and circulatory systems. In total, 72 anomalous twins (46%) and 116 normal co-twins (74%) were delivered at a median gestational age of 34.6 weeks (IQR 31.0–36.3). Neonatal/infant death of the anomalous twin occurred in 22 cases (14%), with an overall survival rate of 32% (50/155). Surviving anomalous twins underwent major surgery in 22/50 cases (44%), four of whom (8%) now suffer from severe neurologic morbidity. This study shows that a wide spectrum of major discordant structural anomalies can be found in monochorionic pregnancies. The outcome for the anomalous twin is poor, while the survival rate for the normal co-twin was 71%, with a favorable overall prognosis.